Design and evaluation of collagen-inspired mineral-hydrogel nanocomposites for bone regeneration. (August 2020) - Patel, Akhil; Zaky, Samer H.; Schoedel, Karen; Li, Hongshuai; Sant, Vinayak; Beniash, Elia; Sfeir, Charles; Stolz, Donna B.; Sant, Shilpa
Abstract: Bone loss due to trauma and tumors remains a serious clinical concern. Due to limited availability and disease transmission risk with autografts and allografts, calcium phosphate bone fillers and growth factor-based substitute bone grafts are currently used in the clinic. However, substitute grafts lack bone regeneration potential when used without growth factors. When used along with the added growth factors, they lead to unwanted side effects such as uncontrolled bone growth. Collagen-based hydrogel grafts available on the market fail to provide structural guidance to native cells due to high water-solubility and faster degradation. To overcome these limitations, we employed bioinspired material design and fabricated three different hydrogels with structural features similar to native collagen at multiple length-scales. These hydrogels fabricated using polyionic complexation of oppositely charged natural polysaccharides exhibited multi-scale architecture mimicking nanoscale banding pattern, and microscale fibrous structure of native collagen. All three hydrogels promoted biomimetic apatite-like mineral deposition in vitro elucidating crystalline structure on the surface while amorphous calcium phosphate inside the hydrogels resulting in mineral-hydrogel nanocomposites. When evaluated in a non-load bearing critical size mouse calvaria defect model, chitosan - kappa carrageenan mineral-hydrogel nanocomposites enhanced bone regeneration without added growth factors compared to empty defect as well as widely used marketed collagen scaffolds. Histological assessment of the regenerated bone revealed improved healing and tissue remodeling with mineral-hydrogel nanocomposites. Overall, these collagen-inspired mineral-hydrogel nanocomposites showed multi-scale hierarchical structure and can potentially serve as promising bioactive hydrogel to promote bone regeneration. Statement of Significance: Hydrogels, especially collagen, are widely used in bone tissue engineering. Collagen fibrils play arguably the most important role during natural bone development. Its multi-scale hierarchical structure to form fibers from fibrils and electrostatic charges enable mineral sequestration, nucleation, and growth. However, bulk collagen hydrogels exhibit limited bone regeneration and are mostly used as carriers for highly potent growth factors such as bone morphogenic protein-2, which increase the risk of uncontrolled bone growth. Thus, there is an unmet clinical need for a collagen-inspired biomaterial that can recreate structural hierarchy, mineral sequestration ability, and stimulate recruitment of host progenitor cells to facilitate bone regeneration. Here, we propose collagen-inspired bioactive mineral-hydrogel nanocomposites as a growth factor-free approach to guide and enhance bone regeneration. Graphical Abstract: Image, graphical abstract